The Gramm-Rudman-Hollings act: More revisions? - Barbara Kauffmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
During the first half of the eighties, the U.S. federal deficit rose from 74 bn to 212 bn. When the Congressional Budget Office (CBO) projected in August 1985 that the deficit would further increase to 285 bn by 1990, the Gramm-Rudman-Hollings Act (GRH Act) was put into law. Its purpose is to help the government with cutting the deficit, even more, to force it into doing so. Congress and the president put themselves into this confined situation by voting for and signing the bill, respectively, because they realized that their differences in budget priorities would continue to cause budget deadlocks. The GRH Act specifies deficit targets for each year which decline at equal steps to reach zero in the final year, which is now supposed to be 1993. There have been deficit targets before, but they were regularly passed over in the budget process. This is not possible now, because the sequestration procedure,- the prominent feature of the GRH Act, requires that federal government expenditures - on defense and nondefense likewise - be cut automatically if the regular budget process does not reduce the federal budget deficit to the specified amount.
Keywords: 330; Öffentliche Schulden; USA; Haushaltskonsolidierung